Nerve growth factors prevent glutamate toxicity in cortical neuronal cultures - Lin Ling; Zhang He-Yun; Gu Hai-Ming; Tang Guo-Zhi; Zhang Zu-Xuan; Wang Jin-Xi; Zhang Wei-Ning; Chen Rong-San (Acta Pharmacologica Sinica, 2016)
AIM: To determine if nerve growth factors (NGF) can protect against glutamate-induced cortical neuron damage. METHODS: Neuron viability and lactate dehydrogenase (LDH) efflux in the bathing medium in primary cultures from 17-d-old mouse fetal cortex were measured to assay NGF effect. Imaging of the calcium indicator dye Fura-2 was used to measure the [Ca2+]i. RESULTS: The LD50 for NGF-free glutamate was 0.2 mmol.L-1 (95% confidence limits 0-1.6 mmol.L-1). In the presence of NGF 60 micrograms.L-1, 59% of the neurons survived in glutamate 1.6 mmol.L-1. The protective effect afforded by NGF was maximal at 60 micrograms.L-1, at which it prevented the elevation in [Ca2+]i. CONCLUSION: NGF protect cortical neurons against glutamate-induced toxicity via ""stabilizing"" [Ca2+]i level or suppression of the rise in [Ca2+]i.